COMPLETE RESOLUTION OF SUBHYALOID HEMORRHAGE WITH ND: YAG HYALOIDOTOMY: A CASE REPORT - Fricella, Ais; Fadillah, Yasin; Noerdiyani, Niken Indah (International Journal of Research -GRANTHAALAYAH, 2025)
Background: Subhyaloid hemorrhage is a vision-threatening condition commonly caused by retinal vascular disorders, trauma, or systemic diseases such as hypertension and diabetes mellitus. Management strategies vary, ranging from observation to surgical interventions. Nd: YAG laser hyaloidotomy has emerged as a minimally invasive therapeutic option that allows for rapid drainage of premacular blood into the vitreous cavity, thus accelerating visual recovery. Case Presentation: We report the case of a 17-year-old girl who experienced acute, painless vision loss in her right eye after a Valsalva maneuver. Fundus examination revealed a dense, boat-shaped premacular hemorrhage consistent with subhyaloid hemorrhage. Nd: YAG laser hyaloidotomy was performed using a posterior capsulotomy lens and a single 3.5 mJ pulse to puncture the posterior hyaloid face. Immediate drainage of blood into the vitreous cavity was observed. Over a follow-up period of eight weeks, complete resolution of hemorrhage and significant improvement of visual acuity (from counting fingers at 4/60 to 6/6) were documented. Conclusion: Nd: YAG hyaloidotomy represents an effective, safe, and minimally invasive therapeutic approach for selected cases of subhyaloid hemorrhage. This case underscores the importance of timely intervention in preventing prolonged visual impairment and highlights the role of laser therapy as an alternative to invasive vitreoretinal surgery.